Effect of Urea Variation Concentration on Slow Release Fertilizer (SRF) Based Chitosan/NaTPP/Calcium - Wijayanti, Alvia Rachma; Cahyaningrum, Sari Edi (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
Environmental pollution due to urea can negatively impact the environment and its surroundings. Efforts to prevent environmental pollution include encapsulating urea made of chitosan/NaTPP/Ca, which aims to determine its physical and chemical properties. This study crosslinks chitosan 1.66%, with NaTPP 3.33%, CaO, with variations in the addition of urea concentrations of 0.05%, 0.1%, 0.15%, 0.2%, and 0.25%. The results of FTIR characterization showed that there were functional groups OH-, C-H, Ca-O, NH, and P=O. The membrane weight yield ranges from 0.14-0.16 grams, while the average membrane thickness is 0.15-0.35 mm. The water absorption test is 1.86-2.64%, and the membrane porosity result is 0.91-2,25%. This shows that the membrane with a base material of 1.66% chitosan and 3.33% NaTPP is the best.